2008
DOI: 10.1002/art.23451
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of monocyte and lymphocyte messenger RNA expression with serum protein profiles in patients with scleroderma

Abstract: Objective. We attempted to elucidate possible pathogenetic mechanisms in scleroderma by analysis of gene expression patterns of purified monocytes and lymphocytes, as well as protein profiles of cytokines and growth factors.Methods. Expression analysis was performed on messenger RNA (mRNA) from cells that had been purified with magnetic beads. Plasma samples from the same patients were used for multiplex cytokine analysis. Potential sources of proteins were also examined by in situ hybridization of skin specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
88
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 46 publications
16
88
1
Order By: Relevance
“…In line with findings in SLE, data on an IFN type I signature are growing [134][135][136] and a recent report from Kim et al [137] showed interferogenic activity by antitopo I ICs. Although a role for type I IFNs in SSc is counterintuitive knowing that these IFN are potent inhibitors of collagen production in fibroblasts [138], a report describing the rapid onset of SSc symptoms in patients treated with intense IFN therapy suggests a clear pathologic contribution of IFNs to the development of SSc [139].…”
Section: Systemic Sclerosissupporting
confidence: 62%
See 1 more Smart Citation
“…In line with findings in SLE, data on an IFN type I signature are growing [134][135][136] and a recent report from Kim et al [137] showed interferogenic activity by antitopo I ICs. Although a role for type I IFNs in SSc is counterintuitive knowing that these IFN are potent inhibitors of collagen production in fibroblasts [138], a report describing the rapid onset of SSc symptoms in patients treated with intense IFN therapy suggests a clear pathologic contribution of IFNs to the development of SSc [139].…”
Section: Systemic Sclerosissupporting
confidence: 62%
“…[10] Increased transcription of certain type I IFN regulated genes in peripheral blood cells. [135] Endogenous TLR4ligands in serum. [39] Myeloid APCs in diseased skin.…”
Section: In Vivomentioning
confidence: 99%
“…[6][7][8] Using gene sets from public data 9 (Supplementary Table 2), here we provide evidence that type I rather than type II IFNs are responsible for the increased expression of IFN-induced genes. This was validated with specific type I and II IFN gene sets from Baechler et al 10 (Supplementary Table 3).…”
Section: Disease Profiling In Ssc CL Bos Et Almentioning
confidence: 84%
“…The most significant upregulated process that distinguished SSc patients from controls was 'interferon (IFN)-mediated immunity,' which is a subgroup of the ontology group 'immunity and defense' (Figure 1, cluster B, indicated with b1). [6][7][8] Other biological processes that were upregulated in patients compared with healthy individuals within this cluster were: 'protein metabolism and modification,' 'nucleoside, nucleotide and nucleic acid metabolism' and 'apoptosis.' Genes in cluster C genes were related to 'cell cycle,' and those in cluster D to 'signal transduction' and 'immunity and defense.'…”
Section: Gene Expression Profiling In Pb Cells Of Ssc Patientsmentioning
confidence: 99%
“…The quality of RNA was assessed for each sample using an Agilent 2100 Bioanalyzer (Agilent Technologies, Palo Alto, CA). cRNA preparation, probe labeling, and chip hybridization was performed as previously described (17). Labeled cRNA was hybridized to the Sentrix MouseRef-8 Expression BeadChip v1.0a (Illumina, San Diego, CA).…”
Section: Microarray Analysismentioning
confidence: 99%